The Effect of Global Prices of Crude Palm Oil, Marketing Margins and Palm Oil Plantations on the Environmental Destruction: An Application of Johansen Cointegration Approach - Syahril, Syahril; Masbar, Raja; Syahnur, Sofyan; Majid, Shabri A.; Zulham, T.; Saputra, Jumadil; Badli, Saiful; Irmayani, Irmayani (International Journal of Energy Economics and Policy, 2019)
As the most important factor in the world, palm oil is a crucial element that contributed to economic growth of a country. Besides as a role of the important vegetables oil, palm oil also gives a negative effect on environment through expanding the palm oil plantation. Therefore, this study aims to investigate the effect of global crude palm oil (CPO) price, marketing margins, and palm oil plantations on environmental destruction in the short-term and long-term. For examining the short-term and long-term effect, this study used Johansen Cointegration approach involving the bivariate causality with the Pirwise Granger Causality test and multivariate causality relationships with the Wald test. Also, we analyzed the responds of independent variables to dependent variable using impulse response (IRF) and variance decomposition (VD). This study used a monthly secondary data starting on 2008 to 2017 i.e. Environmental Quality Index, Global CPO price, Marketing margins and palm oil plantations. The data collected from 5 sources i.e. Central Bureau of Statistic (BPS), Food and Agriculture Organization (FAO), World Trade Organization, Central Bank of Indonesia (BI) and the Central Bank of Malaysia (BNM). The results of analysis shows that there is long-term relationship of global CPO price, marketing margins, and palm oil plantations on environmental quality index. For short run, this study found that global CPO price has a significant positive effect on environmental quality index. Meanwhile, the size of palm oil plantation and marketing margins have a significant negative effect on environmental quality index in Indonesia. Also, using the bivariate test, this study proves that there is one way causality relationship between the global CPO prices, marketing margins and size of oil palm area on environmental quality index. In addition, the global CPO prices and marketing margins fluctuations causing shock in environmental quality index. Keywords: Global Crude Palm Oil Prices, Marketing Margin, Palm Oil Plantations, Environmental Quality Index JEL Classifications: C01, C50, Q43, Q51 DOI: https://doi.org/10.32479/ijeep.8010